Neighbourhood design and Vmt: is Malaysia planning to achieve the spirit of new urbanism? - Majid, Mohammad Rafee (2012)
Urban population currently represents sixty eight percents of the total population of Malaysia, doubling its value of thirty three percents in 1970. By the year 2020, when Malaysia plans to achieve industrialised-nation status, about two thirds of the population will be in urban areas living in mass-produced housing schemes first constructed in the 1970s. Although travel modes have changed significantly in Malaysia along with the changes in the physical design of these housing areas, very little is known about how the changes influence household vehicle-mile-travelled or VMT. The effects of neighbourhood design on VMT are an important aspect to consider in our effort to reduce greenhouse gas emission. Thus, this paper presents the findings of a study carried out in the City of Johor Bahru, within the designated economic growth area of Iskandar Malaysia, to understand how the change in neighbourhood designs over the decades due to policies and lifestyles influences VMT. Fifty two residential neighbourhoods representing several decades from 1970s to the 2000s were selected and travel diaries of their randomly selected households were recorded. While the results obtained confirm the prevalent theory on the relationship between neighborhood design and VMT, unfortunately for the study area the average VMT has been increasing with the newlydesigned neighborhoods. Increasing wealth and mobility apparently has seen increasing demand for neighborhood designs that are not as compact as the traditional ones and not as ‘mixed uses’ either. While the rest of the world is going for ‘new urbanism’, Malaysia which embraced its form of ‘new urbanism’ called ‘mixed development’ since 1970s is doing the opposite. As population of Johor Bahru is rapidly growing due to its location in the economic growth area of Iskandar Malaysia, serious rethinking of the current development policies is in order.